A neurodevelopmental disorder associated with an activating de novo missense variant in ARF1 - Ishida, Morié; Otero, María G; Freeman, Christina; Sánchez-Lara, Pedro A; Guardia, Carlos M; Pierson, Tyler Mark; Bonifacino, Juan S (Human molecular genetics, 2023)
Abstract ADP-ribosylation factor 1 (ARF1) is a small GTPase that regulates membrane traffic at the Golgi apparatus and endosomes through recruitment of several coat proteins and lipid-modifying enzymes. Here, we report a pediatric patient with an ARF1-related disorder because of a monoallelic de novo missense variant (c.296 G > A; p.R99H) in the ARF1 gene, associated with developmental delay, hypotonia, intellectual disability and motor stereotypies. Neuroimaging revealed a hypoplastic corpus callosum and subcortical white matter abnormalities. Notably, this patient did not exhibit periventricular heterotopias previously observed in other patients with ARF1 variants (including p.R99H). Functional analysis of the R99H-ARF1 variant protein revealed that it was expressed at normal levels and properly localized to the Golgi apparatus; however, the expression of this variant caused swelling of the Golgi apparatus, increased the recruitment of coat proteins such as coat protein complex I, adaptor protein complex 1 and GGA3 and altered the morphology of recycling endosomes. In addition, we observed that the expression of R99H-ARF1 prevented dispersal of the Golgi apparatus by the ARF1-inhibitor brefeldin A. Finally, protein interaction analyses showed that R99H-ARF1 bound more tightly to the ARF1-effector GGA3 relative to wild-type ARF1. These properties were similar to those of the well-characterized constitutively active Q71L-ARF1 mutant, indicating that the pathogenetic mechanism of the R99H-ARF1 variant involves constitutive activation with resultant Golgi and endosomal alterations. The absence of periventricular nodular heterotopias in this R99H-ARF1 subject also indicates that this finding may not be a consistent phenotypic expression of all ARF1-related disorders.